Three new species of Protosticta Selys, 1885 (Odonata: Zygoptera: Platystictidae) from the Western Ghats, India, with taxonomic notes on P. mortoni Fraser, 1922 and rediscovery of P. rufostigma Kimmins, 1958 - Joshi, Shantanu; Subramanian, K.a.; Babu, R.; Sawant, Dattaprasad; Kunte, Krushnamegh (Zootaxa, 2020)
Three new species of Protosticta Selys, 1885 (Odonata: Zygoptera: Platystictidae) from the Western Ghats biodiversity hotspot in India: P. cyanofemora sp. nov. (wet evergreen forests in Shendurney Wildlife Sanctuary, Kollam, Kerala and Kalakkad Mundanthurai Tiger Reserve, Tirunelveli, Tamil Nadu), P. myristicaensis sp. nov. (Myristica swamp at Kathalekan, Shivamogga, Karnataka) and P. sholai sp. nov. (montane sholas of Upper Manalar, Meghamalai Wildlife Sanctuary, Theni, Tamil Nadu) are described and illustrated. We compare these three new species with other Protosticta spp. from the Western Ghats based on new material and provide comprehensive differential diagnoses with determination key for males of all species occurring in the Western Ghats. The taxonomic validity of P. mortoni Fraser, 1922 is established with fresh specimens from Hassan, Karnataka, and rediscovery of P. rufostigma Kimmins, 1958 is reported from Kanyakumari Wildlife Sanctuary, Tamil Nadu.